RELIEF TERRA SIGILLATA FROM CIBALAE (VINKOVCI, NORTH-EASTERN CROATIA) - Leleković, Tino (Rei Cretariae Romanae Fautorum Acta, 2024)
Roman Cibalae (present-day Vinkovci) is situated in the north-eastern part of Croatia. During the Roman period this area belonged to the south-eastern part of the province of Pannonia. It seems that the geographical position of Cibalae was crucial for its expansion and for the development of its strategic and economic importance. Cibalae was founded on the river Bosut, a relatively small confluent of the Sava River, in the region surrounded by the rivers Sava, Drava and Danube. All of the major transport through this region was most probably carried out by those rivers. The town of Vinkovci is situated on a narrow elevation between the Požega Mountains on the west side and Fruška Mountain on the east. An essential feature for the understanding of the importance of the area in question throughout antiquity is the fact that the regions south and north of the mentioned elevation were swamps covered with dense oak forests. The elevation was therefore a kind of an isthmus through those swamps, providing a safe communication during the season of floods. Owing to that, the location of the town of Cibalae was a densely inhabited spot since the beginning of the Neolithic and throughout all prehistoric periods. Before the final Roman occupation which occurred in the beginning of the 1st century AD, the area of Vinkovci was occupied by a large Celtic settlement. Upon the arrival of the Romans Romanizing procedures were introduced on all levels, turning Cibalae into a typical Roman town.